Bidirectional Relationships Between School Connectedness and Internalizing Symptoms During Early Adolescence. (November 2020) - Klinck, Melanie; Vannucci, Anna; Ohannessian, Christine McCauley
School connectedness is an important feature to consider within the school environment because it likely accounts for why some youth thrive and others struggle with internalizing problems. Furthermore, internalizing problems typically do not occur in isolation of each other, but rather anxiety and depressive symptoms frequently co-occur and increase subsequent risk for each other. As such, the primary study objectives were to (a) evaluate the bidirectional relationships between school connectedness and internalizing symptoms and (b) examine whether being at high risk of an anxiety disorder or major depression moderated these relationships. Adolescents attending public middle schools ( N = 1, 344; 11-14 years; 51% female; 52% White) completed surveys in school at baseline and at a 6-month follow-up. Baseline anxiety disorder risk status moderated the relationships between school connectedness and internalizing symptoms. Among adolescents at low risk of an anxiety disorder, higher baseline school connectedness predicted improvements in depressive symptoms and, conversely, higher baseline depressive symptoms predicted lower school connectedness. School connectedness and depressive symptoms were unrelated among adolescents at high risk of an anxiety disorder. There were no significant associations between school connectedness and anxiety symptoms, regardless of baseline risk for major depression. Implications for school-based intervention strategies are discussed, such as fostering school connectedness and screening for internalizing problems.